Soil organic carbon dynamics along chrono-sequence land-use systems in the highlands of Ethiopia - Abegaz, Assefa; Tamene, Lulseged D.; Abera, Wuletawu; Yaekob, Tesfaye; Hailu, Habtamu; Nyawira, Sylvia S.; Silva, Mayesse Aparecida da; Sommer, Rolf (Elsevier, 2020)
Soil organic carbon (SOC) dynamics along land-use changes influences the terrestrial and global carbon cycle, the climate, soil fertility, agricultural productivity, and food security. Taking soils under native forests as an appropriate ecological reference, we studied changes in soil organic carbon stock along eight land-use types in the highlands of Ethiopia. The general objective of the study was to investigate the dynamics of SOC stock following chrono-sequence land-use/cover systems in the highlands of Ethiopia. The specific objectives were to: (1) analyze loss due to land degradation; (2) analyze gain due to land restoration; and (3) estimate partial balance of SOC stock for the highlands of Ethiopia. The study followed the principle of the Forest Transition Theory (FTT). Eleven sub-areas were considered from the highlands of Ethiopia. A total of 241 auger composite samples from the topsoil (0−20 cm depth) were collected during December 2017 to June 2018, and analyzed at CropNut soil lab in Nairobi. The study results revealed that there were statistically significant variations (P < 0.05) across the land-use types with the mean stocks ranging from 31.4 Mg SOC ha−1 in soils of intensively grazed lands to 145.0 Mg SOC ha−1 in soils of guasa grasslands. Soils of natural/pristine vegetation and protected guasa grasslands contain the highest amount of SOC stock. Therefore, there should be more aggressive efforts towards an effective protection of these ecosystems. Soils under intensively used croplands and intensively grazed lands lost, respectively, 64.95% and 78.16%, SOC stocks originally accumulated in the top surface layers of the pristine forests. This points for the need to adopt locally feasible land management practices that lead to increased SOC stock and simultaneously reduced CO2 and greenhouse gas emissions from croplands and intensively grazed lands of the highlands of Ethiopia. Compared to stocks of SOC of intensively grazed lands (31.44 Mg SOC ha−1), the annual stock gains in soils of controlled grazing lands (4.60 Mg ha−1) were > gains in soils of enclosures (3.17 Mg ha−1) > gains in soils of afforestation (2.35 Mg SOC ha−1), which signifies that converting degraded lands to either controlled grazing lands, enclosures, or afforestation would be a promising practice for an enhanced carbon sequestration across the highlands of Ethiopia. This practice is in line with the United Nations’ Sustainable Development Goals. The estimated regional partial stock balance revealed that the loss and gain ratio was 35.1 in 1991, and it declined to 15.4 in 2001, 2.2 in 2011 and 1.8 in 2015. These decreasing ratios indicate the possibility of closing the gap between the losses and the gains in the near future, and eventually shifting to higher rates of gains than losses. It is also important to note that determined efforts towards the effective protection of natural forests and the creation of enclosures and reforestation areas by local communities for enhanced carbon sequestration will benefit them from payments of carbon emission reduction (CER) credits.